La revocación de la suspensión de la ejecución de la pena por incumplimiento del pago de la reparación civil en las sentencias de la corte superior de justicia de la libertad en los años 2012-2014 y el principio de proporcionalidad. - Alvarez Rodríguez, Anghela Leidy (2016)
The present investigation is limited to the fact that to revoke the suspension of the execution of the sentence for noncompliance with the payment of civil damages violates the principle of proportionality. In our country so that the Judge grants the suspension of the conditionality of the sentence first verifies compliance with the formal requirements provided for in Article 57 of our Penal Code. The first of them establishes that the prognosis of the sentence should not be more than four years. The second, that the nature, modality of the punishable act, procedural behavior and the personality of the agent, allow to infer that the convict will not commit a new crime. Finally, the third and last requirement requires that the agent does not have the condition of recurrent or habitual. After verifying compliance with the formal requirements set forth in the preceding paragraph, the criminal judge must establish the rules of conduct set forth in article 58 of our substantive code, through which they impose duties and / or obligations on the convicted person under test . However, in paragraph 4 of that article, it is stated that repairing the damages caused by the crime or complying with its fractional payment qualifies as a rule of conduct, which means that if a convicted person is imposed as a rule of conduct, Payment of the civil reparation and this does not comply with it, its sole non-compliance would bring as an immediate consequence that the suspension of the sentence be revoked and that it be interned in a penitentiary center, regardless of for example that it has complied with the other rules of conduct, Reducing everything to the fact whether or not to pay civil reparation, contributing to the de-socialization of the sentenced and the application of a maximum criminal law. With respect to the antecedents we have found a wide bag of information contained in theses that deal with aspects of the problematic proposal and doctrine where the majority of authors is inclined by the disproportionality of the injurious measure. Having as justification the determination of whether the guidelines outlined by the judges at the time of revoking the suspended sentence in the event of non-payment of civil compensation constitutes an assumption of breach of the principle of proportionality or an infringement of the principle of prohibition of prison for debt, and Provide the necessary guidelines that contribute to the violation of the right to freedom of the accused and not denaturalize the institution of civil liability arising from a crime. For this purpose, we have as a proposed problem the following: Does the revocation of the suspension of the execution of the sentence, due to failure to pay civil compensation in the sentences of the Superior Court of Justice of La Libertad in the years 2012 to 2014, The Principle of Proportionality? In development we have dealt as the first chapter with theories of punishment, inasmuch as it is fundamental to determine whether the injurious measure does not know the special preventive purpose of punishment. As a second chapter we develop a complete analysis of the suspension of the conditionality of punishment, because it is necessary to determine the purpose of the implementation of this measure substitute. As a third chapter entitled civil reparation, we will develop the main doctrinal drafts on the nature of civil reparation and its development in our jurisprudence. In addition, as the penultimate chapter, the principle of proportionality was addressed, as it is fundamental for the development of our investigation, addressing The analysis of the three sub-principles and as a last point we have agreed to add the chapter entitled criminalization of poverty, while it has been verified that the people who have been revoked the suspension of the sentence argue that they do not have the economic means To make the payment. The development of the hypothesis constitutes that the revocation of the suspension of the sentence for noncompliance with the payment of civil damages violates the principle of proportionality, since it makes the enforcement of the custodial sentence dependent on a civil and / or formal matter Of short duration, reducing everything to verify if the sentenced canceled or not a sum of money in favor of the aggrieved, without taking into account the other requirements that allowed the Judge to suspend the sentence, and above all overlooking the special preventive purpose that Pursue this measure. With regard to the objectives of the present investigation, it is necessary to determine whether the revocation of the suspension of the sentence for failure to pay civil compensation violates the principle of proportionality. With regard to the results and discussion of results, we have that the injurious measure, that is to say, the revocation of the suspension of the execution of the sentence for noncompliance with the payment of civil reparation, is not a necessary measure insofar as it violates the right to freedom of the Sentenced; Who had previously been suspended in order to avoid short prison sentences; There is an alternative and equally effective means of achieving integral reparation to the victim, since it would be possible to use a precautionary measure such as the embargo, which the criminal procedural code establishes in order to guarantee the payment of civil damages and also We have that the majority of judges in the judicial district La Libertad during the years 2012-2014 at the moment of solving the requirements of revocatoria of the suspension of the execution of the sentence by noncompliance of the payment of the civil reparation declares founded what was intended by the Ministry Public.